Thermoeconomic considerations in the allocation of heat transfer inventory for irreversible refrigeration and heat pump systems. (June 2015) - Qureshi, Bilal Ahmed; Zubair, Syed M.
Abstract: In this paper, thermoeconomic considerations are given to heat exchanger inventory allocation in irreversible refrigeration cycles and heat pumps with finite thermal capacitances. Investigation is made with respect to specified rate of cooling and heating for the refrigeration cycle and heat pump, respectively. Exact expressions are obtained without the use of an internal irreversibility parameter. The optimum hot-to cold-end unit cost ratio resulted in unequal division of heat exchanger conductances for the heat pump in contrast to the endoreversible case where they were the same. At a constant evaporator to condenser fluid temperature ratio, the COP of both refrigeration and heat pump systems was found to vary in an almost asymptotic manner in contrast to the endoreversible case where it was constant. In conclusion, it is best to measure the effect of internal dissipation by deriving exact mathematical expressions as the effect on some performance parameters could be lost due to the averaging effect of the internal irreversibility parameter. Highlights: Thermoeconomic optimization of heat exchanger inventory in irreversible cycles is studied. Analysis is carried out both for cooling and heating applications with finite thermal capacitances. Analytical expressions are obtained for different operating conditions. The optimum cost ratio results in unequal division of heat exchanger conductances for the heat pump.